DIFFERENTIAL HEAT OF ADSORPTION OF AMMONIA ON LTA CEOLITE - Bazarbayev M.; Juraeva Z.; Mamadaliev U. (Innovate Conferences, 2025)
This paper presents the results of differential heat of adsorption of ammonia in Ca5Na3A zeolite (MSS-624) at a constant temperature of 303 K. A system consisting of a universal high-vacuum adsorption unit coupled to a Tiana-Calvet type differential microcalorimeter, DAK-1-1A, was used to measure the differential heat of adsorption. A correlation between adsorption-energy characteristics was found, and the molecular mechanism of ammonia adsorption in Ca5Na3A zeolite (MSS-624) in the whole filling region was also revealed. A stepwise change in the differential heat of adsorption depending on the amount of Na+ and Ca2+ cations in the zeolite has been established. Ammonia molecules initially form tetrameric ion-molecular complexes 4NH3:Na+ in the first coordination sphere with sodium cations and monomeric ion-molecular complexes 2NH3:Ca2+ with calcium cations
Keywords: adsorption, heat, enthalpy, thermodynamics, microcalorimeter, ammonia, adsorption mechanism, cation, sodium, calcium.